Methodology of Teaching Biology, Legislative Aspects - Lola Narmatovna Egamberdieva; Aziza Khabibullaeva (Zien Journals, 2023)
Biological education is of great importance in the life of mankind. The biology teacher must have a deep understanding of the life and work of every person of the biological knowledge, make sure of it and educate this confidence in the students. The profession of a biology teacher requires a high level of knowledge and strong willpower, so that students can absorb why every person needs to learn biology. In this paper, the integrity of the biological education process, teaching printouts and legislation are studied
Keywords: Education; Science; Biology; Ecology